The Effect of Paired Variation Exercises on Improve Passing Accuracy and Coordination in Football - Azmi Syaiful Azhar; Anggi Setia Lengkana; Entan Saptani (Universitas Tadulako, 2026)
The objective of this study is to investigate the effectiveness of paired variation exercises on the accuracy and coordination of passing football among pupils of primary schools. One-group pretest-posttest research design was applied for this study. For the purpose of the study, 30 pupils from elementary school grades 4 and 5 were selected using purposive sampling technique. Tests utilized in this study include short passing accuracy test and passing coordination test. Paired variation exercises made up the treatment done for twelve sessions. Data collected were subjected to statistical analysis by applying normality and homogeneity tests, paired samples t-tests and coefficient of determination. Significant improvements were observed with regards to passing accuracy and passing coordination after the exercise. This was determined by observing the results of paired samples t-test whose significance value was less than 0.05 in both cases. Therefore, it can be concluded that paired variation exercises have statistically significant effects on the passing abilities of students playing football. Furthermore, paired variation exercises are significantly effective in improving passing coordination with coefficient of determination of 82.7%.